Alkali-activation of metakaolin and blast furnace Portland cement blends - Mesquita Campinho de Azevedo, Cláudio; Márcio de Araújo Santana, Cléo; Feuchard Mansur, Luccas; Fernandes Côrtes Pires, Eliane; Feliciano Soares Filho, Paulo; Chahdan Mounzer, Elie; José da Silva, Felipe (Seven Editora, 2023)
The addition of certain pozzolanic materials to Portland cement significantly changes the properties of the hardened matrix. If it has too high content of blast furnace slag, as the case of blast furnace Portland cements (BFPC), the early and late compressive strengths can be severely delayed or reduced. The objective this work was to investigate the potential of alkali-activation of BFPC and metakaolin (MK) blends by different types and contents of alkali-activators. The results clearly showed the influence of the MK pozzolanic activity and the type and content of activator used, in the development of compressive strengths of BFPC-MK blends. Microstructural analysis by SEM/EDS, DSC and XRD shown that the consumption of portlandite and the extra formation of C-S-(A)-H phases are the main positive effects registered. However, MK also promotes the formation of ettringite and unstable hydrated calcium aluminate phases, which, with the course of hydration, undergo a change in structure and volume loss, contributing to the reduction of final strengths. Content of 25% MK and 7.5% Na2SiO3 provided the best mechanical strength. The microstructures formed showed greater formation of ettringite, however there was also a reduction in portlandite and massive formation of C-S-H and C-S-(A)-H products. DOI: https://doi.org/10.56238/tfisdwv1-010